An analysis of institutions and policy processes for selected antipoverty interventions in Bangladesh - Ahmed, Akhter; Khondkar, Mubina (International Food Policy Research Institute, 2010)
This study attempts to provide an understanding of how the process of institutional change influences the outcomes of interventions. To better understand the context in which these interventions took place, the study examines the institutional aspects of new agricultural technology interventions and the policy processes of food- and cash-based education incentive programs. The institutional analysis pays special attention to issues of institutional origins, persistence, and transformation. The paper then examines the motivation and policy processes of the Food for Education program and its subsequent replacement, the cash-based Primary Education Stipend program. The study reviews similarities and differences among selected antipoverty interventions according to their pro-poor orientation, attention to gender issues, extent of involvement of other partners, attention to sustainability, and the use of research and evaluation to inform organizational change.